2016
DOI: 10.1007/978-3-319-50349-3_2
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Assisted Feature Computation for Continuous Problems

Abstract: A possible approach to Algorithm Selection and Configuration for continuous black box optimization problems relies on problem features, computed from a set of evaluated sample points. However, the computation of the features proposed in the literature require a rather large number of such sample points, unlikely to be practical for expensive real-world problems. On the other hand, surrogate models have been proposed to tackle the optimization of expensive objective function. It is proposed in this paper to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…However, all aforementioned works used a large sample size (≥ 500 × d) to compute features. And as expected, the error of computing the features increases the budget decreases, as demonstrated with a limited budget of ≤ 100 × d in [6,20]. This drawback can be somehow limited by building a surrogate model f from S and gathering further samples using f without additional evaluations of f [6,20].…”
Section: Features For Continuous Domainmentioning
confidence: 70%
See 4 more Smart Citations
“…However, all aforementioned works used a large sample size (≥ 500 × d) to compute features. And as expected, the error of computing the features increases the budget decreases, as demonstrated with a limited budget of ≤ 100 × d in [6,20]. This drawback can be somehow limited by building a surrogate model f from S and gathering further samples using f without additional evaluations of f [6,20].…”
Section: Features For Continuous Domainmentioning
confidence: 70%
“…The computation of features is the core element of the empirical performance model and its predictive power. Belkhir et al [6] had empirically shown that the accuracy of the feature critically depends on their computational costs. The present study was focused on low budgets to compute features.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations